Stance and Belief System of a Researcher in Qualitative Research: Philosophies and Paradigms - Devi Prasad Bhattarai (Interdisciplinary Research in Education, 2021)
This paper provides an idea on why novice researcher needs to understand the basic philosophy and paradigm of their underlying research problem. The paper aims to provide insights into research philosophies and paradigms so that a researcher could locate his/her research in a qualitative inquiry. To draw on the idea, the paper exemplarily utilizes my qualitative study of the doctoral program as an example which makes a needy researcher clearer in his/her philosophical arguments and worldviews and makes him/her position in a qualitative study. Methodologically, the paper is the product of a series of texts written centering onthe qualitative research published by internationally renowned publishers, and the texts were selected by the discussion and talk about the philosophical texts during the doctoral student’s seminars.The paper basically argues that a researcher needs to become clear about the research problem he/she is undertaking about research philosophy – ontology, epistemology, and methodology – and the paradigm in which his/her research problem rests. By this understanding, a researcher expectedly locates his/her research study appropriately with his/her underlying philosophical stance and belief system in a qualitative study.